The use of a dual-articulation acetabular cup system to prevent dislocation after primary total hip arthroplasty: analysis of 384 cases at a mean follow-up of 15 years - Philippot, Remi (Springer-Verlag, 2008)
The concept of a dual articulation acetabular cup was developed by Prof. Bousquet in 1974. This concept has been shown to provide high stability after revision and primary total hip arthroplasty. The aim of our study was to evaluate the incidence of prosthetic instability in a consecutive homogeneous series of 384 primary dual mobility cups. Incidence of instability and implant survival were evaluated. Mean follow-up was 15.3 years (range, 12–20). There was no early or late instability. On the acetabular side there were 13 aseptic loosenings, 14 intraprosthetic dislocations, and seven polyethylene wear cases that required replacement of the liner. The cumulative survival rate of the dual-articulation acetabular cup using surgical revision for aseptic loosening as the endpoint was 95.9% ± 4.1% at 18 years postoperatively. Our series proves the good long term behaviour of dual-articulation acetabular components in primary arthroplasty. Their excellent survivorship rate and the absence of episodes of prosthetic instability increase our confidence in this concept.